2019
DOI: 10.3390/ijms20122920
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Efficient Genetic Transformation Systems and Application of CRISPR/Cas9 Genome Editing Technology in Lilium pumilum DC. Fisch. and Lilium longiflorum White Heaven

Abstract: Lilium spp. is a bulb flower with worldwide distribution and unique underground organs. The lack of an efficient genetic transformation system for Lilium has been an international obstacle. Because existing model plants lack bulbs, bulb-related gene function verification studies cannot be carried out in model plants. Here, two stable and efficient genetic transformation systems based on somatic embryogenesis and adventitious bud regeneration were established in two Lilium species. Transgenic plants and T-DNA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 64 publications
0
46
0
2
Order By: Relevance
“…Transformation conditions are key elements affecting the transformation efficiency which in turn affect the protein expression. Agrobacterium concentration or cell density is one of such factors that affect the efficiency of plant transformation; low concentration may result in insufficient Agrobacterium infection, whereas high concentration can cause the plant cell damage or trigger hypersensitive response leading to plant tissue necrosis [ 41 , 42 ]. We found that Agrobacterium cell density at the OD 600 of 0.2 was found to be optimal for plant transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Transformation conditions are key elements affecting the transformation efficiency which in turn affect the protein expression. Agrobacterium concentration or cell density is one of such factors that affect the efficiency of plant transformation; low concentration may result in insufficient Agrobacterium infection, whereas high concentration can cause the plant cell damage or trigger hypersensitive response leading to plant tissue necrosis [ 41 , 42 ]. We found that Agrobacterium cell density at the OD 600 of 0.2 was found to be optimal for plant transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Petunia has been edited with CRISPR-Cas9 targeting various traits, including an albino phenotype [ 155 ], flower longevity [ 156 ], deficiency in nitrate assimilation [ 157 ], and self-incompatibility [ 158 ]. The LpPDS gene in two Lilium species was successfully edited resulting in albino, pale yellow, and albino-green chimeric mutants [ 159 ]. Multiple MADS genes have been targeted in Phalaenopsis for flower initiation and development [ 160 ].…”
Section: Breeding For Anthocyaninsmentioning
confidence: 99%
“…Two genetic transformation systems, such as somatic embryogenesis and adventitious bud regeneration, have been established for the application of CRISPR-Cas9 technology in two Lilium species, L. longiflorum and L. pumilum. By targeting the phytoene desaturase (PDS) gene encoding a key enzyme of carotenoid synthesis for induced mutagenesis, mutant Lilium species of the albino, pale-yellow, and albino-green chimeric types were produced with various patterns of mutation, including base insertion, deletion, and substitution [58]. In addition, some results from orchid studies using CRISPR-Cas systems for genome editing have been recently released.…”
Section: Current Status Of Genome Editing In Ornamental Plantsmentioning
confidence: 99%